Primary Fixation and Cyclic Performance of Single-Stitch All-Inside and Inside-Out Meniscal Devices for Repairing Vertical Longitudinal Meniscal Tears. Issue 10 (August 2022) - Bachmaier, Samuel; Krych, Aaron J.; Smith, Patrick A.; Herbort, Mirco; Ritter, Daniel; LaPrade, Robert F.; Wijdicks, Coen A.
Background: Primary device fixation and the resistance against gap formation during repetitive loading influence the quality of meniscal repair. There are limited biomechanical data comparing primary tensioning and cyclic behavior of all-inside versus inside-out repair. Hypothesis: All-inside devices provide higher initial load on the meniscal repair than inside-out fixation, and stiffer constructs show higher resistance against gap formation during cyclic loading. Study Design: Controlled laboratory study. Methods: In total, 60 longitudinal bucket-handle tears in human cadaveric menisci were created and repaired with a single stitch and randomly assigned to 4 all-inside groups (TrueSpan, FastFix 360, Stryker AIR, FiberStich) and 2 inside-out groups (suture repair [IO-S], suture tape [IO-ST]). Residual load after repair tensioning (50 N) and relief displacement were measured. Constructs underwent cyclic loading between 2 and 20 N over 500 cycles (0.75 Hz) with cyclic stiffness, gap formation, and final peak elongation measured. Ultimate load and stiffness were analyzed during pull to failure (3.15 mm/s). Results: All-inside repair demonstrated significantly higher primary fixation strength than inside-out repair. The significantly highest load (mean ± SD; 20.1 ± 0.9 N; P < .037) and relief displacement (–2.40 ± 0.32 mm; P < .03) were for the knotless soft anchoring FiberStich group. The lowest initial load (9.0 ± 1.5 N; P < .001) and relief displacement (–1.39 ± 0.26 mm; P < .045) were for the IO-S repair group. The final gap formation (500th cycle) of FiberStich (0.75 ± 0.37 mm; P < .02) was significantly smaller than others and that of the IO-S (1.47 ± 0.33 mm; P < .045) significantly larger. The construct stiffness of the FiberStich and IO-ST groups was significantly greater at the end of cyclic testing (16.7 ± 0.80 and 15.5 ± 1.42 N/mm; P < .042, respectively) and ultimate failure testing (23.4 ± 3.6 and 20.6 ± 2.3 N/mm; P < .005). The FastFix 360 (86.4 ± 4.8 N) and Stryker AIR (84.4 ± 4.6 N) groups failed at a significantly lower load than the IO-S group ( P < .02) with loss of anchor support. The FiberStich (146.8 ± 23.4 N), TrueSpan (142.0 ± 17.8 N), and IO-ST (139.4 ± 7.3 N) groups failed at significantly higher loads ( P < .02) due to suture tearing. Conclusion: Overall, primary fixation strength of inside-out meniscal repair was significantly lower than all-inside repair in this cadaveric tissue model. Although absolute differences among groups were small, meniscal repairs with higher construct stiffness (IO-ST, FiberStich) demonstrated increased resistance against gap formation and failure load. Clinical Relevance: Knotless single-stitch all-inside meniscal repair with a soft anchor resulted in less gapping, but the overall clinical significance on healing rates remains unclear.